Cash Waqf Intention among Indonesian Muslim Youth: The Role of Banking Digitalization - Haidar, Abdullah; Hendrasto, Nur; Herindar, Evania; Chairiyati, Fauziah (SMART Insight, 2024)
This study aims to explore the factors influencing the adoption of cash waqf transactions by Generation Z and Millennials in East Java, Indonesia, focusing on the use of the Digital Sharia Banking System (DSBS). Implemented through a collaboration between the Badan Wakaf Indonesia (BWI) and Sharia banks utilizing financial technology (FinTech), DSBS represents an innovative approach to facilitating cash waqf transactions. The investigation involved 200 participants and utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the data. The results indicate that the overall model met all the requirements. Key findings suggest that the decision or intention of Generation Z and Millennials in East Java to participate in waqf through DSBS is influenced by factors such as convenience, usefulness, and subjective norms. The study highlights that the ease and benefits of using DSBS for cash waqf transactions are the most crucial factors driving the growth of cash waqf in the region. Integrating the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), the research reveals that while perceived usefulness is a significant driver for positive attitudes and intentions to use DSBS, ease of use and behavioral control do not significantly impact these attitudes or intentions. Therefore, enhancing the perceived usefulness of DSBS is recommended as a more effective approach to promote its use in waqf transactions.